Spatial Model of Carbon Stocks in Special Purpose Forest Area (KHDTK) Mungku Baru, Central Kalimantan Province, Indonesia - Hanafi, Nanang; Jauhari, Ahmad; Hatta, Gusti Muhammad; Hafizianor (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
This study aims to estimate vegetation biomass and spatial distribution of carbon stocks in Special Purpose Forest Area (KHDTK) Mungku Baru, Palangka Raya City, Central Kalimantan Province, Indonesia. KHDTK Mungku Baru is a former logging area from the 1970s, which has undergone secondary succession and is dominated by pole and sapling levels. The approach used in this study involves remote sensing technology and field inventory data, which allows carbon stock calculations to be carried out quickly and accurately over a very large area. A linear regression algorithm was used to obtain a spatial model of carbon stocks using NDVI obtained from Landsat as a predictor. The developed model shows positive correlation results with an R2 value of 0.70; an Adjusted R2 value of 0.69 with a p-level < 0.05, and RMSE of 42 tons/ha. This carbon stock mapping results serve as a basis for formulating various management plans for KHDTK Mungku Baru regarding ecological, social, and economic aspects. Keywords: carbon stocks, normalized difference vegetation index, spatial model, special purpose forest area, vegetation biomass